Microbiota and mobile genetic elements influence antibiotic resistance genes in dust from dense urban public places. (15th October 2022) - Feng, Tianshu; Han, Qian; Su, Wanghong; Yu, Qiaoling; Yang, Jiawei; Li, Huan
Abstract: Many contaminants were carried by dust, a common environment media that is easy to contact with human beings, and antibiotic resistance genes (ARGs) as an emergency pollutant also harbor in dust and pose serious threats to human health especially those carried by opportunistic pathogens because inactivation of antibiotics caused by ARGs may enhance pathogenicity. Considering there is a gap of investigation of dust ARGs, 16 S rRNA gene sequences and high-throughput quantitative PCR were employed to obtain information of microbial communities and accumulated ARGs in dust from different urban places, including the malls, hospitals, schools and parks, to investigate the distribution and influencing factors of ARGs and discover the potential hosts of ARGs in dust. Here, 9 types of ARGs such as sulfonamide, tetracycline, and beta-lactamase and 71 subtypes of ARGs like sul1, tetM-01, and drfA1 were detected in dust. ARGs had varying distribution in different public places and seasons in dust. The abundances of total ARGs, MLSB and tetracycline genes were higher in spring than summer. The diversity of ARGs was highest in malls, follow by hospitals, schools, and parks. Additionally, multi-drug resistance genes in dust were more abundant in hospitals than in schools and parks. The microbes were distinguished as the most important driving factors for ARGs in dust, followed by the mobile genetic elements (MGEs) and different places, while dust physicochemical parameters only exert a negligible impact. Notably, several opportunistic pathogens like the Streptococcus, Vibrio, and Pseudomonas were inferred as potential hosts of high-risk ARGs such as mecA, tetM-02, and tetO-01 in dust because of strongly positive co-occurrence. These results imply that dust is likely an important reservoir of ARGs. We should realize that ARGs may be harbored in some opportunistic pathogens occur in dust and endanger human health because of dust contacting to human easily. Graphical abstract: Image 1 Highlights: Many common ARGs harbored in dust from various public places. Diversity of dust ARGs were higher in spring than those in summer. Microbiome was the leading driving factors of ARGs, followed by different places and MGEs. Some high-risk ARGs and opportunistic pathogens were found in dust. Several high-risk ARGs presented positive correlations with opportunistic pathogens.